Inovasi Frozen Food Patin, Qr Code Terintegrasi Aplikasi Camilan Cegah Stunting - Pridayanti, Anggie; Dahriansah, Dahriansah; Apridonal, Yori (J-Com (Journal of Computer), 2025)
Abstract: Stunting remains a significant chronic nutritional problem in Indonesia, with a prevalence of 21.6% in 2023. The primary cause is a lack of balanced nutritional intake from an early age. This research aims to develop an innovative healthy food product in the form of frozen food made from nutrient-rich catfish and moringa leaves, integrated with a QR Code system into the "KA OLIF" application. This application provides educational information on how to prepare and the nutritional benefits of healthy snacks, aimed at increasing parental awareness of children's consumption patterns. The research method used was descriptive qualitative through observation, interviews, and literature studies. The results of the system development show that the integration of QR Code technology and educational applications can facilitate the delivery of information in a practical and interactive manner. This innovation not only provides a healthy food solution but also serves as an educational medium that supports the government's program to reduce stunting rates. By utilizing local potential such as catfish and moringa leaves, along with digital technology, this product is expected to reach a wider community and improve nutritional understanding from an early age. Keywords: stunting; frozen food; nutrition fortification; QR code; ka olif application. Abstrak: Stunting masih menjadi salah satu permasalahan gizi kronis yang signifikan di Indonesia, dengan prevalensi mencapai 21,6% pada tahun 2023. Penyebab utamanya adalah kurangnya asupan gizi seimbang sejak usia dini. Penelitian ini bertujuan untuk mengembangkan inovasi produk makanan sehat berbentuk frozen food berbahan dasar ikan patin dan daun kelor yang kaya akan nutrisi, serta diintegrasikan dengan sistem QR Code menuju aplikasi “KA OLIF”. Aplikasi ini menyediakan informasi edukatif mengenai cara penyajian dan manfaat gizi camilan sehat, yang ditujukan untuk meningkatkan kesadaran orang tua terhadap pola konsumsi anak. Metode penelitian yang digunakan adalah kualitatif deskriptif melalui observasi, wawancara, dan studi literatur. Hasil dari pengembangan sistem menunjukkan bahwa integrasi teknologi QR Code dan aplikasi edukatif dapat mempermudah penyampaian informasi secara praktis dan interaktif. Inovasi ini tidak hanya menghadirkan solusi pangan sehat, namun juga menjadi media edukatif yang mendukung program pemerintah dalam menurunkan angka stunting. Dengan pemanfaatan potensi lokal seperti ikan patin dan daun kelor, serta teknologi digital, produk ini diharapkan mampu menjangkau masyarakat luas dan meningkatkan pemahaman gizi sejak dini. Kata kunci: stunting; frozen food; fortifikasi gizi; QR code; aplikasi ka olif